Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]t-(7-3t)+5=2t+10\ \ \ \ \ | omit\ the\ bracket\\\\
t-7+3t+5=2t+10\\\\
4t-2=2t+10\ \ \ | subtract\ 2t\\\\
2t-2=10\ \ \ | add\ 2\\\\
2t=12\ \ \ \ | divide\ by\ 2\\\\
t=6[/tex]
t-(7-3t)+5=2t+10
combine like terms for each side first
(7-4t)-5=2t+10
than combine like terms to one side to make the variable positive
(7)-5=6t+10
next combine like terms to the other side( just the number not the variable
7-5-10=6t
now you simplify again
-8=6t
than you divide both sides by 6 to get t(the variable) by it self
-1[tex] \frac{1}{3} [/tex]=t
combine like terms for each side first
(7-4t)-5=2t+10
than combine like terms to one side to make the variable positive
(7)-5=6t+10
next combine like terms to the other side( just the number not the variable
7-5-10=6t
now you simplify again
-8=6t
than you divide both sides by 6 to get t(the variable) by it self
-1[tex] \frac{1}{3} [/tex]=t
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.